Oncoplastic breast conserving surgery versus standard breast conserving surgery for early and locally advanced breast cancer: a retrospective analysis from Sri Lanka - Kanchana Wijesinghe; Thilanka Abeywickrama; Yohan Chamara; Sumali De Silva; Sebastianpillai Tharshan; Umesh Jayarajah; Ajith De Silva (BMC Surgery, 2023)
Abstract Background Breast aesthetics is becoming increasingly important in breast cancer surgery due to changes in patient expectations and greater emphasis been placed on the psychosocial outcomes. Studies have shown no difference in local recurrence risk between mastectomy and breast conserving surgery (BCS) and also a higher overall survival rate after BCS. Breast preservation improves the quality of life substantially compared to mastectomy. Oncoplastic breast-conserving surgery (O-BCS) involves tumour excision whilst overcoming the limitations of standard breast conserving surgery (S-BCS) by allowing larger resection volumes, avoiding deformities with better aesthetic results. Our study aims to compare the oncosurgical and aesthetic outcomes of O-BCS versus S-BCS among women in Sri Lanka. Methods We conducted a retrospective study over a 4-year period including patients who underwent breast conservation surgery for primary non-metastatic breast cancer in two tertiary care units. We assessed outcomes in terms of re-excision rates, resection margin, complications and aesthetic outcomes using a Likert scale questionnaire to grade specific outcomes such as symmetry, volume, nipple position, scar visibility. Non-parametric tests were used for statistical analyses. Results Fifty-four and seventy-three patients underwent S-BCS and O-BCS respectively. The median specimen volume and the maximum tumour diameter were significantly higher in O-BCS [160(range:65–220); 4.2(range: 1.2–5.2)] compared to S-BCS [65(range:45–86); 2.4(range: 1.0-2.6)]. The median closest tumour margin was 16 mm (range:4-25 mm) in O-BCS while 6 mm (range:<1 – 12 mm) in S-BCS (p = 0.01). Close (< 1 mm) and positive margins needing re-excision were seen mostly in S-BCS. Superior aesthetic outcomes with statistical significant difference were reported in the O-BCS compared to S-BCS group with better symmetry, volume, nipple position and scar visibility. The re-excision rates were significantly lower in O-BCS group. There was no significant difference in the operative time and complications while the aesthetic outcomes were significantly superior in OBCS. Conclusions Overall, Level 2 perforator flap based reconstruction had superior aesthetic outcomes. O-BCS is safe and more aesthetically acceptable with no difference in oncological outcome and operative time. More consideration should be given to aesthetic parameters such as scar visibility, nipple position, breast volume and shape when considering the best surgical option for the patients.